(untitled) (Economics and region, 2025)
In the context of global transition, the issue of the balanced growth and a more unified, integrated EU turns into an existential challenge to the regional bloc. The goal of the paper is to analyze the dynamics of the nominal GDP per capita of the EU nations, as well as to examine the dynamics of the ratio of the GDP per capita of the individual EU countries to the average GDP per capita in the EU with the aim of coming up with suggestions in terms of reducing the differences existing between the levels of the socio-economic development within the EU. To achieve the goal, various methods have been used, including those of the experts’ assessments, comparative analysis, tabular representation, logical generalization, etc. The data for the analysis is taken from the official site of the UNCTAD. The results show that there is still significant differentiation in the state and dynamics of development among the EU nations. The dependence of the implementation of the principle of the supremacy of the EU law over national law on the formation of a common identity of the citizens in the union is justified. In the context of preserving national identity in the regional bloc, decisions taken at the level of the regional organization that may give advantages to some member states at the expense of other member states, which are at the basis of equalizing the development of the countries, may exacerbate tense relations within the regional union. The existence of a common identity levels out the national characteristics of the member states of the bloc and thus makes such tensions in relations between them impossible. It is substantiated that in order to improve the cohesion of the EU nations it is necessary to pay special attention to the effectiveness and the quality of the functioning of the EU supranational governing bodies, which should be guided by the interests of the union as a whole, rather than the interests of individual, in particular, the most powerful nations of the union. The strengthening of supranationality in the EU is directly dependent on the formation of a common identity for the bloc, which will become the basis for the formation of the union’s sovereignty as a single entity, rather than a mechanical sum of the sovereignties of individual member states. At the same time the EU currency system needs further development, with the euro zone expanding to all the EU member states and the euro becoming more widely used in international settlements, strengthening its position as a global reserve currency.